Halal Tourism: Trend, Opportunities, Challenges and Impact of Halal Tourism on Conventional Tourism - Muharis; M. Saidi; Dani Alfatwari; Ahmad (Sumber Belajar Sejahtera, 2023)
This study aims to analyze and find out how the trend of halal tourism in the West Nusa Tenggara region and its impact on conventional tourism is investigated. The results of this study show first, the trend of halal tourism in terms of opportunities and challenges, the opportunity for halal tourism in West Nusa Tenggara is very large seeing the intensity of visits every year is so high, especially middle eastern tourists. This is a business investment opportunity for the country's economic income. However, regulations on aspects of halal certification for accommodation and tourism products such as hotels, restaurants and cafes are still an obstacle in the development of halal tourism. Secondly, the presence of halal tourism does not necessarily change and shift pre-existing conventional tourism, but halal tourism is present as a complement and supporter in the expansion of services and facilities to tourists who visit both in terms of accommodation and all the needs of tourists in general.